Current Status and Future Prospects of Adaptability Verification and Evaluation Methods for Rapid Grain Testing Instruments - SHI Jing-rui; LAN Sheng-bin; SHI Heng; DONG De-liang; LI Wei; ZHANG Yu-rong (Liang you shipin ke-ji)
In the field of grain quality and safety supervision, the rapid advancement of new technologies and quick-detection instruments have made ensuring their accuracy and reliability an urgent industry need. This paper integrates existing methods for verifying the applicability of rapid grain testing instruments and introduces various outlier analysis techniques. A novel evaluation method is proposed improving the instruments' ability to identify and process anomalous data. This establishes a scientific and reliable approach to verifying and evaluating their applicability, which is crucial for ensuring the accuracy and reliability of test results. The paper also explores future research directions in field of rapid grain testing instrument verification, aiming to refine evaluation methods and advance their practical application.